Using TOPSIS and AHP Methods in Job Distribution to Subcontractors in Apparel Companies and Comparing the Results - KAYAR, MAHMUT (INST CHEMICAL FIBRES, 2021)
The ready-to-wear sector is one of the areas where outsourcing is used extensively due to reasons such as being a labour-intensive sector, having a wide range of products, and the time pressure caused by the very short shelf life of the product. Therefore, garment companies work with a large number of subcontractors, which raises the problem as to which subcontractor/subcontractors work will be distributed to as well as how much to each subcontractor. Using multi-criteria decision-making methods in solving this complex problem helps decision-makers make the right decisions. From this point of view, multi-criteria decision-making methods are very important decision-making tools in terms of the optimal distribution of work to subcontractors. Within the scope of the study, the TOPSIS and AHP methods were used to distribute orders to subcontractors and compared.
Keywords: Multi criteria decision making; MCDM; job distribution; supplier selection; TOPSIS; AHP; apparel; FUZZY AHP; SELECTION